Next-Generation Sequencing of Antibody Display Repertoires - Rouet, Romain; Jackson, Katherine J. L.; Langley, David B.; Christ, Daniel (Frontiers in Immunology, 2018)
In vitro selection technology has transformed the development of therapeutic monoclonal antibodies. Using methods such as phage-, ribosome- and yeast-display, high affinity binders can be selected from diverse repertoires. Here we review strategies for the next generation sequencing (NGS) of phage- and other antibody-display libraries, as well as NGS platforms and analysis tools. Moreover, we discuss recent examples relating to the use of NGS to assess library diversity, clonal enrichment and affinity maturation.